Leadership Styles in Strengthening Lecturers Motivation for Academic Rank Advancement at Private Universities in Gorontalo Province - Masran Biahimo; Udin Hamim; Lisda Van Gobel (Journal of Scientific Insights, 2026)
Academic rank advancement known in Indonesia as jabatan fungsional serves as one of the clearest markers of a lecturer's professional growth, yet a substantial proportion of lecturers at private universities in Gorontalo Province have yet to pursue it. This study examined how different leadership styles relate to lecturer motivation in pursuing academic rank, and what factors stand in the way. Using a qualitative case-study approach, data were gathered through in-depth interviews, direct observation, and document review at STIKES Bakti Nusantara Gorontalo and Universitas Gorontalo. Findings reveal that authoritarian leadership, when applied without adequate support structures, tends to generate compliance rather than genuine motivation. Charismatic and transformational styles, by contrast, foster a sense of belonging and professional pride that encourages lecturers to take career development seriously. Transactional approach esparticularly when reward systems are clear and fairly applied also show positive results, though their effect is contingent on institutional consistency. Four key inhibiting factors were identified: limited leadership attention toward individual lecturers, inadequate welfare and remuneration, poor understanding of the academic rank process, and an underdeveloped reward system. The study concludes that sustainable motivation for academic rank advancement requires a combination of inspirational leadership, fair compensation, and institution-wide literacy about career pathways.